2013
DOI: 10.1136/jfprhc-2013-100687
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for coitally-dependent hormonal contraception: perspectives from women in urban Kenya and Nigeria

Abstract: Introduction Emergency contraceptive pills (ECPs) were developed and marketed with the emergency aspect firmly in mind, but research and anecdotal evidence indicate that some women use them as a form of regular contraception, spurring efforts in the reproductive health community to explore the development of a coitally-dependent oral contraceptive pill. Methods We asked women of reproductive age in Nairobi, Kenya and Lagos, Nigeria how likely they would be to use a hypothetical pericoital pill and why. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Within the study, women who have infrequent sex demonstrated a high degree of satisfaction and intent to use the method in the future. This aligns well with previous studies, which demonstrated demand and acceptability with a theoretical method (e.g., Chin‐Quee, L'Engle, and Otterness 2014; Cover et al. 2013a) and within actual study conditions (i.e., Festin et al.…”
Section: Discussionsupporting
confidence: 91%
“…Within the study, women who have infrequent sex demonstrated a high degree of satisfaction and intent to use the method in the future. This aligns well with previous studies, which demonstrated demand and acceptability with a theoretical method (e.g., Chin‐Quee, L'Engle, and Otterness 2014; Cover et al. 2013a) and within actual study conditions (i.e., Festin et al.…”
Section: Discussionsupporting
confidence: 91%
“…Communication messages would best respond to ECP users’ needs by encouraging the view that frequent users of ECPs are engaging in safe, responsible behaviour that will not harm their future fertility. Because the majority of ECP users are typically young 4 , 7 and may be more likely to use an on-demand contraceptive product, 26 it is particularly important that ECP communication directed towards pharmacists and drug shop staff supports repeated use among young women as a safe and responsible choice.…”
Section: Discussionmentioning
confidence: 99%
“…Papers reported on research conducted in 16 countries across five WHO regions: nine countries in Africa, including Benin [ 29 ], the Democratic Republic of Congo (DRC) [ 35 ], Ethiopia [ 26 , 31 ], Ghana [ 11 , 33 , 36 , 38 , 39 ], Kenya [ 12 , 27 , 28 , 30 ], Nigeria [ 27 , 28 , 30 , 32 ], Somalia [ 34 ], Uganda [ 37 ] and Zambia [ 39 ]; three countries in the Americas, including the US [ 42 , 44 ], Brazil [ 40 , 43 , 45 ] and Argentina [ 41 ]; two countries in South East Asia, including India [ 46 , 48 , 49 ] and Nepal [ 47 ]; one country in Eastern Mediterranean, in Iran [ 50 ]; and two countries in Europe, in Spain [ 52 ] and Serbia [ 51 ]. One paper reported on data from multiple international settings [ 10 ]; no research was identified from the Western Pacific.…”
Section: Resultsmentioning
confidence: 99%
“…The reviewed papers used qualitative ( n = 12) [ 26 , 31 , 32 , 34 37 , 39 , 40 , 42 , 44 , 49 ], quantitative survey ( n = 14) [ 27 30 , 33 , 38 , 41 , 43 , 45 48 , 50 , 51 ], intervention or trial ( n = 3) [ 10 12 ] and surveillance ( n = 1) [ 52 ] approaches. Twenty four papers reported on the perspectives of end users (e.g., younger women, women of reproductive age, university students, male sexual partners) [ 10 12 , 26 39 , 41 44 , 49 , 52 ], nine papers on service providers (e.g., pharmacists, GPs, clinicians, midwives, community health workers) [ 26 , 34 , 40 , 45 48 , 50 , 51 ], and four on other stakeholders (e.g., donors, policy makers, NGO workers) [ 26 , 34 , 37 , 46 ].…”
Section: Resultsmentioning
confidence: 99%